The Platformization of the Web: Making Web Data Platform Ready - Helmond, Anne (Social media + society, 2015)
In this article, I inquire into Facebook’s development as a platform by situating it within the transformation of social network sites into social media platforms. I explore this shift with a historical perspective on, what I refer to as, platformization, or the rise of the platform as the dominant infrastructural and economic model of the social web and its consequences. Platformization entails the extension of social media platforms into the rest of the web and their drive to make external web data “platform ready.” The specific technological architecture and ontological distinctiveness of platforms will be examined by taking their programmability into account. I position platformization as a form of platform critique that inquires into the dynamics of the decentralization of platform features and the recentralization of “platform ready” data as a way to examine the consequences of the programmability of social media platforms for the web.